Epistemologi Pendidikan Agama Islam: Integrasi Sumber Transenden dan Rasional dalam Pembentukan Kesadaran Religius Peserta Didik - Gondo Adhi Saputra; Bambang Triawan Pamungkas; Nur Naria Dina Romadhon; Akmalun Najmi; Muhammad Wahyudi Azzukhruf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Religious Education in the modern era faces an epistemological challenge in the form of a dichotomy between transcendent sources (revelation) and rational sources (reason and empirical experience), which often gives rise to a normative-dogmatic or, conversely, rationalistic-secular learning approach. This condition impacts the weak formation of students' religious awareness that is complete, reflective, and contextual. This study aims to analyze the epistemological integration of transcendent and rational sources in Islamic Religious Education and its implications for the formation of students' religious awareness. This study uses a qualitative approach with a literature review method of primary and secondary sources in the form of the Qur'an, hadith, works of interpretation, books on Islamic educational philosophy, and relevant journal articles. Data collection techniques are carried out through documentation and systematic searches of literature that has conceptual and theoretical relevance. Data analysis uses a thematic and interpretative analysis model by linking the concepts of Islamic epistemology, educational theory, and the objectives of Islamic Religious Education. Data validity is maintained through triangulation of sources, theories, and perspectives of expert thought. The research results show that the integration of the epistemology of revelation and reason in Islamic Religious Education forms a learning paradigm that not only instills normative beliefs but also encourages critical reasoning, moral reflection, and contextual spiritual awareness. Students' religious awareness does not stop at ritual obedience but develops into a responsible ethical and social awareness. The implications of this research emphasize the importance of developing an Islamic Religious Education curriculum and learning strategies that integrate transcendent and rational dimensions in a balanced manner to develop religious, critical, and civilized students in modern life. Keywords: Epistemology of Islamic Religious Education, Integration of Revelation and Reason, Religious Awareness.